Treatment of child offenders under the Child Rights Law of Lagos State in some selected custodial institutions - Nwanna, Chinwe R.; Ogunniran, Iyabode (Advances in Social Sciences Research Journal, 2021)
The main objective of this study was to assess the care of children and child offenders in particular under the Child Rights Law (CRL) of Lagos State in some selected custodial institutions. The study adopted a triangulation approach to collect both primary and secondary data from four purposefully selected Special Correctional Centres between 7th July and 30th September, 2013. Social welfare officers in charge of these custodial institutions were interrogated. Findings revealed that only two Special Children’s Centres had child offenders. Other results include poor living conditions, inadequate recreational facilities, regular visits from parents/guardians and formal and informal education as stipulated in section 52 and 224 (1) of CRL respectively. Major challenges were poor data base, poor security of the premises, shortage of skilled staff and lack of funds and awareness of the services of custodial institutions. Organisation of awareness campaigns, recruitment and capacity building for staff, improvement of living conditions to meet the CRL standard, among others, are recommended.